Efectos de estilos de crianza sobre la depresión en adolescentes escolarizados de una muestra peruana - Castro Renteria, Eliana V. (2022)
The objective of this research was to determine the influence exerted by parenting styles on the depression of Peruvian schooled adolescents. For this, a sample of 308 high school students was used, between men (47.1 %) and women (52.9 %), who had an average age of 14.5 years (SD = 2.218). It has a non-experimental, empirical design of associative strategy, classified within an explanatory study. To measure the chosen study variables, the following were used: the Family Parenting Styles Scale (ECF-29) and the Patient Health Questionnaire (PHQ-9); both with solid evidence of validity and reliability. The results of the structural equation model analysis revealed that 42 % (r2=.42) explains the variance of depression and 65 % (r2=.65) explains the variance of parenting styles. In addition, the best predictor of depression is the overprotective style (β=.43), followed by the authoritarian (β=.18) and indulgent (β=.17) style; unlike the democratic style, which does not explain depression in adolescents in a relevant way (β= - .09). It is concluded that depression is being explained with greater intensity by the common characteristics of the overprotective parenting style, while the democratic parenting style does not do so significantly.